Comparison of pregnancy outcome after adding oral or intramuscular progesterone to vaginal progesterone in frozen embryo transfer: A cross-sectional study - Sahereh Arabian; Maryam Eftekhar; Saeideh Dashti; Nahid Homayoon; Elham Nikfarjam (International Journal of Reproductive BioMedicine, 2024)
Background: Currently, frozen embryo transfers (FET) account for 41% of all embryo transfer cycles. Vaginal progesterone preparations have become the leading choice for luteal phase support due to their convenient application; however, using only vaginal progesterone during FET cycles results in a lower ongoing pregnancy rate.